Communication Model in Agricultural Zakat Counseling in Nagari Sungai Tarab - Khalid, Imam; Mita, Monica Helva (Semantik: Journal of Social, Media, Communication, and Journalism, 2023)
Basically, extension is a communication activity. Zakat extension communication is a form of process of conveying information to the relevant community, systematically, planned and directed in order to change behavior and opinions of the relevant community. The communication process carried out by zakat counselors to the relevant communities is not solely due to the transfer of information from communicator to communicant but how the message conveyed by the communicator reaches the communicant properly. So that awareness arises from the communicants to try and apply the information they get. In accordance with the aim of counseling itself, namely to help the community to have knowledge about everything related to zakat and to provide a modern view and new paradigm about zakat which is a need for the community. The formulation of the problem in this research is What is the Communication Model used by the instructor? zakat in Nagari Sungai Tarab? Meanwhile, the aim of this research is to determine the mode of communism carried out by agricultural zakat instructors in Nagari Sungai Tarab. This research uses field research with qualitative descriptive methods. The data collection techniques that researchers used were field observations, interviews and documentation. The reason researchers use qualitative descriptive research is to obtain data and understand the phenomena experienced by informants. The results of this research state that there are two communication models that have been used by researchers in the agricultural zakat extension process in Nagari Sungai Tarab. Namely the Linear communication model and the Interactional communication model, each communication used is very influential in this research where these two communications function to convey information to the relevant community in a systematic, planned and directed manner for the sake of sustainably changing the behavior and opinions of the relevant community. The related community is muzaki. Meanwhile, the communication model in agricultural zakat counseling consists of an individual approach, a group approach and a mass approach